PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. THAMRIN BROTHER YAMAHA LEBONG - Mulyadi, Regi; Islamuddin, Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2025)
The title of this research is The Influence of Leadership Style and Motivation on Employee Performance at PT. Thamrin Brother Yamaha Lebong. A company engaged in buying and selling motorbikes and spare parts. This research was conducted in December 2023 with respondents from all employees of PT. Thamrin Brother Yamaha Lebong totaling 34 respondents. In collecting data using a questionnaire which was then processed using the SPSS application, this research used multiple linear analysis techniques with a quantitative descriptive research type. From the research results, it is known that the Leadership Style variable influences employee performance, this is proven by the results of data testing which shows the value of tcount > ttable (3,045>1,693) data obtained from the field. The motivation variable influences employee performance, this can be seen from the test results where tcount > ttable (2,326>1,693) data obtained from the field. Where the value of the f test results for the variables of leadership style and motivation together influence the performance of PT employees. Thamrin Brother Yamaha Lebong with a significance value of 0.000 < 0.05.Keywords: Leadership Style, Motivation and Employee Performance